ALIEN FLORA FROM BUZĂU COUNTY – ROMANIA (Acta Horti Botanici Bucurestiensis, 2024)
In this paper, we provided the first checklist of alien flora of Buzău County (Romania). Our study revealed the positive invasion trend during recent years. 110 alien taxa were recorded, who belong to 36 families of vascular plants, 52 of them being invasive. The Americas, Asia and the Mediterranean area are the main regions of origin of the taxa of the inventory. Three species are of European Union concern: Ailanthus altissima, Asclepias syriaca and Elodea nuttallii. The most alien plant species were recorded for Buzău and Râmnicu-Sărat cities.